Splat! - Burgerman, Jon (New York, NY : Dial Books for Young Readers, 2017)
Encourages the reader to predict what will happen and keep turning pages as a face is splattered with a pie, a sandwich, and more.
"Originally published in the United Kingdom by Oxford University Press, 2017."
Keywords: Humorous stories; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Interactive Adventures; JUVENILE FICTION / Art & Architecture